Comparative homology model building and docking evaluation for RNA III inhibiting peptide of Multi drug resistant Staphylococcus aureus strain MRSA252. (April 2018) - Mevada, Vishal; Patel, Rajesh; Patel, Bhoomi; Chaudhari, Rajesh
Graphical abstract: Highlights: Present work has been carried out to get the structural insight with various online and offline homology modeling techniques such as SWISS-MODEL, MODBASE, GENO3D, CPHmodels and I-TASSER for getting unknown structural information target of RNAIII-activating protein from Staphylococcus aureus strain MRSA252 origin for their future exploration as a target in drug discovery process against MRSA. We have evaluated best possible methods to modeled the best structure amongst all six different platforms. The results for virtual screening also supports the hypothesis regarding the Modeled structure created in study. The interaction analysis for binding pattern includes maximum 8 H-bonds and 2 van de waals bonds from a single molecules. This indicates the potential possibility to block RAP protein of S. aureus in in vitro conditions. Abstract: Since last several years, infection caused by Staphylococcus aureus is challenging to cure using conventional antibiotics. The organism is a Gram-positive bacterial pathogen that can cause serious diseases not only in humans but also in animals, such as various skin infections, pneumonia, endocarditis and toxin shock syndrome. This bacterium causes such diseases by producing macromolecules such as hemolysins, enterotoxins, proteases and toxic shock syndrome toxin (TSST-1). This organism had developed the multidrug resistance by acquiring MEC-A gene. This account for made organism to come into the category of Superbug. Several studies showed that, the toxin production is induced by AIP and RAP via the phosphorylation of TRAP. TRAP is a 21 kDa protein and was believed to be associated with the membrane via SvrA Phosphoamino acid analysis revealed that TRAP is histidine phosphorylated in a signal transduction pathway that is activated by RAP. The inhibition of TRAP could be done by RIP (RNAIII-inhibiting peptide). The structure for RIP is still undiscovered to be used as inhibitor. Present work has been carried out to get the structural insight with various online and offline homology modeling techniques such as SWISS-MODEL, MODBASE, GENO3D, CPHmodels and I-TASSER for getting unknown structural information target of RNAIII-activating protein from Staphylococcus aureus strain MRSA252 origin for their future exploration as a target in drug discovery process against MRSA.